A Survey-Based Evaluation of a Multi-Angle Dental Mouth Mirror Among Practicing Dentists - Dr. Akanksha Baheti; Dr. Radhika Tijoriwala; Dr. Riya Shah; Dr. Lidiane Fumiko Takeda (The Bioscan, 2026)
Background: Dental mouth mirrors are essential diagnostic instruments; however, limited visibility in posterior regions and operator fatigue remain common challenges. A multi-angle dental mouth mirror has been proposed to overcome these limitations. Aim: To evaluate dentists’ perception regarding the usefulness, visibility enhancement, ergonomic benefit, and acceptability of a multi-angle dental mouth mirror. Materials and Methods: A cross-sectional questionnaire-based survey was conducted among 100 practicing dentists using Google Forms. The questionnaire consisted of eight close-ended questions assessing clinical experience, perceived usefulness, clinical applications, visibility improvement, operator strain reduction, willingness to use, recommendation likelihood, and purchase intent. Responses were recorded on Likert and categorical scales. Data were analyzed using descriptive statistics. Results: Most participants perceived the multi-angle dental mouth mirror as useful, with high scores for improved visibility and willingness to adopt the design in routine practice. A majority also felt that the design could reduce operator strain. Conclusion: Dentists showed a positive perception toward the multi-angle dental mouth mirror, indicating its potential clinical usefulness, ergonomic advantage, and market acceptability. Keywords Dental mouth mirror, ergonomic dentistry, dental instruments, visibility, survey study